2023
DOI: 10.1186/s12940-023-01003-9
|View full text |Cite
|
Sign up to set email alerts
|

How ambient temperature affects mood: an ecological momentary assessment study in Switzerland

Abstract: Background Recent research has suggested that an increase in temperature can negatively affect mental health and increase hospitalization for mental illness. It is not clear, however, what factors or mechanisms mediate this association. We aimed to (1) investigate the associations between ambient temperatures and bad daily mood, and (2) identify variables affecting the strength of these associations (modifiers) including the time, the day of the week and the year of the mood rating, socio-demog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…In this scenario, we demonstrate here that global warming negatively affects mental health. However, despite the huge magnitude of the problem, the biological mechanisms underlying this association remain unknown and likely involve complex multifactorial relationships [97][98][99] . Some evidence suggests that exposure to hot temperatures may directly affect brain function, with alterations in proper oxygenation and permeability of the blood-brain barrier.…”
Section: Discussionmentioning
confidence: 99%
“…In this scenario, we demonstrate here that global warming negatively affects mental health. However, despite the huge magnitude of the problem, the biological mechanisms underlying this association remain unknown and likely involve complex multifactorial relationships [97][98][99] . Some evidence suggests that exposure to hot temperatures may directly affect brain function, with alterations in proper oxygenation and permeability of the blood-brain barrier.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, one could argue that our thermal perception of the environment has a more important role in regulating our psychosocial aspects than actual physical warmth during work, although these effects were very modest. This effect could be due to the fact that people associate higher temperature conditions with the opportunity to go out and be involved in more social activities [ 25 , 53 ]. However, other variables, for example the availability of other people to go out, can further influence the outcomes, suggesting the presence of combined effects, which supports the modest direct effect of the thermal perception on psychosocial variables.…”
Section: Discussionmentioning
confidence: 99%
“…However, this study did not control for the presence of any mental health difficulties reported in the sample taken into consideration. Recent studies investigating the effect of outdoor ambient temperature on mood suggest that individuals with specific mental health difficulties are more prone to negative affect, and potentially to acts of aggression, than individuals with no mental health difficulties when there is an increase in ambient temperature [ 25 ]. According to Bundo, Preisig, Merikangas, Glaus, Vaucher, Waeber, Marques-Vidal, Strippoli, Müller, and Franco [ 25 ], this could be due to the fact that those people might have less opportunities for social activities, which become more prominent under rising temperatures, a weather state that encourages social activities and social connection.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have also shown that extremely high temperature and high humidity can affect emotional and behavioural disorders and increase the number of patients with conditions such as schizophrenia, mania, and neurological disorders 6 . As the problem of global warming further intensifies, the impact of extremely humid heat environments on negative emotions (e.g., anxiety) in humans will increase further, and the impact of environmental changes on mental health has attracted increasing attention 7 , 8 . How climate (e.g., temperature and humidity) changes lead to neuropsychiatric disorders remains largely unknown.…”
Section: Introductionmentioning
confidence: 99%